A mechanistic PK/PD model to enable dose selection of the potent anti‐tryptase antibody (MTPS9579A) in patients with moderate‐to‐severe asthma. Issue 4 (8th February 2023) - Rymut, Sharon M.; Henderson, Lindsay M.; Poon, Victor; Staton, Tracy L.; Cai, Fang; Sukumaran, Siddharth; Rhee, Horace; Owen, Ryan; Ramanujan, Saroja; Yoshida, Kenta
Abstract: Tryptase, a protease implicated in asthma pathology, is secreted from mast cells upon activation during an inflammatory allergic response. MTPS9579A is a novel monoclonal antibody that inhibits tryptase activity by irreversibly dissociating the active tetramer into inactive monomers. This study assessed the relationship between MTPS9579A concentrations in healthy subjects and tryptase levels in serum and nasal mucosal lining fluid from healthy subjects and patients with moderate‐to‐severe asthma. These data were used to develop a mechanistic pharmacokinetic/pharmacodynamic (PK/PD) model that quantitatively inter‐relates MTPS9579A exposure and inhibition of active tryptase in the airway of patients with asthma. From initial estimates of airway tryptase levels and drug partitioning, the PK/PD model predicted almost complete neutralization of active tryptase in the airway of patients with asthma with MTPS9579A doses of 900 mg and greater, administered intravenously (i.v.) once every 4 weeks (q4w). Suppression of active tryptase during an asthma exacerbation event was also evaluated using the model by simulating the administration of MTPS9579A during a 100‐fold increase in tryptase secretion in the local tissue. The PK/PD model predicted that 1800 mg MTPS9579A i.v. q4w results in 95.7% suppression of active tryptase at the steady‐state trough concentration. Understanding how the exposure‐response relationship of MTPS9579A in healthy subjects translates to patients with asthma is critical for future clinical studies assessing tryptase inhibition in the airway of patients with moderate‐to‐severe asthma.